Measuring Production Efficiency in a Not-for-Profit Setting: An Extension. - Mensah, Yaw M.; Li, Shu-Hsing (The Accounting Review, 1993)
Reports on a study that measured production efficiency in a nonprofit organization. Outline of a more complete budgetary system; Comparison of the translog budget model against the applied alternative technique; Reference to a previous study by Hayes and Millar; Decomposition of productive efficiency into technical and allocative components.